Persepsi Masyarakat Terhadap Berhentinya Program Bus Rapid Transit - Wiwit Bayu Adi; Selvia Syafni Safitri (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The research was inspired by the cessation of Bus Rapid Transit program in Mataram which basically the program first goal was to facilitate the Mataram people’s mobility and activities to travel. In addition, the Bus Rapid Transit program, commonly referred to as Trans Mataram Bus, was also aimed to reduce congestion and the number of private vehicles. By reducing the private vehicles on the road, it was expected that the air pollution would also be reduced. The fact that the program is no longer running, considering the large fund spent to build the program and some goals mentioned, this research aim is to find out why the Mataram Bus Rapid Transit program is currently not running using the perception of Mataram people. The research method used Descriptive with a Quantitative approach. The data was taken using observation, interview, literature review and questionnaire. The results show that the Bus Rapid Transit program in Mataram is not working due to the lack of public interest in public transportation services. There are some reasons related which are the Bus Rapid Transit routes or services, at that time, did not cover all areas in Mataram, there is no specific lane for Bus Rapid Transit, the location of the bus stop is far from the residential area and the lack of socialization related to the program so that many communities did not get clear information.